Intelligent decision-making How do the best leaders make the right decisions? : How do you make the right choices in critical situations? (MIT Sloan Management Review, 2018)
"Being able to make decisions with the right balance of speed and information is often what separates successful managers from unsuccessful managers. This collection of articles from MIT Sloan Management Review looks at the decision-making process and the need for good judgement and decisiveness in a variety of circumstances, including times of crisis, situations in which people are facing information overload, and instances when trust has been eroded."--Resource description page.